2003
DOI: 10.1002/nvsm.215
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing ethical climate in a nonprofit organisation: an empirical investigation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 80 publications
3
35
0
Order By: Relevance
“…However, these findings are incongruent with each other. For example, five dimensions extracted by Malloy and Agarwal's (2003) study in the notfor-profit context are individual caring, Machiavellianism, independence, social caring, and law and code. Peterson (2002) suggests the original nine-type model provides a better fit for organizational ethical climate and demonstrates that types of ethical climate have stronger relationships with individual ethical behavior.…”
Section: Dimensions Of Organizational Ethical Climatementioning
confidence: 99%
“…However, these findings are incongruent with each other. For example, five dimensions extracted by Malloy and Agarwal's (2003) study in the notfor-profit context are individual caring, Machiavellianism, independence, social caring, and law and code. Peterson (2002) suggests the original nine-type model provides a better fit for organizational ethical climate and demonstrates that types of ethical climate have stronger relationships with individual ethical behavior.…”
Section: Dimensions Of Organizational Ethical Climatementioning
confidence: 99%
“…Generally speaking, prior research is mixed regarding gender differences in ethics (Malloy and Agarwal, 2003). Theoretical support exists for both sides of the gender differences question (McCuddy and Peery, 1996).…”
Section: Gendermentioning
confidence: 95%
“…Research has demonstrated that ethical perceptions are a significant factor related, among other things, to productivity and satisfaction in organizational members (Cohen, 1995;Malloy and Agarwal, 2003). In this study, we will examine how teachers' perceptions of school ethics are related to an important indicator of teacher productivity: work absence.…”
Section: Teachers' Perceptions Of School Ethicsmentioning
confidence: 97%